Pengaruh Penggorengan Berulang terhadap Kualitas Minyak Goreng - Tri Dyah Astuti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Cooking oil is one of the essential ingredients of everyday life. Cooking oil is made from the mother's acid ester with glycerol. Cooking oil that is used repeatedly can harm health. The use of recurrent oil results in oil damage and affects the quality where the indicator of damage to cooking oil can be seen from the levels of free fatty acids and peroxides. To determine the effect of repeated frying on the quality of cooking oil in terms of the parameters of the levels of free fatty acids and peroxides. The research design used in this study is quantitative with experiments. The cooking oil used is bulk cooking oil and packaged cooking oil used to fry vegetable food ingredients, namely tofu. Numbers of peroxide and free fatty acids can be known through the titration method. The peroxide number test results have increased from the repetition of the third frying to branded oil and second repetition of bulk oil. Peroxide numbers obtained are higher than required by SNI (1.00 mg O2/100g). Examination of the levels of free fatty acids in samples of branded oil and bulk oil shows that all samples are by the oil quality requirements set by SNI (Max. 0.30% b/b).